2006
DOI: 10.1038/nn1802
|View full text |Cite
|
Sign up to set email alerts
|

Propagating waves mediate information transfer in the motor cortex

Abstract: High-frequency oscillations in the beta range (10-45 Hz) are most active in motor cortex during motor preparation and are postulated to reflect the steady postural state or global attentive state of the animal. By simultaneously recording multiple local field potential signals across the primary motor and dorsal premotor cortices of monkeys (Macaca mulatta) trained to perform an instructed-delay reaching task, we found that these oscillations propagated as waves across the surface of the motor cortex along dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

49
500
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(563 citation statements)
references
References 37 publications
49
500
3
Order By: Relevance
“…These measures are similar to propagating neocortical waves observed in vitro (28) and in vivo in visual cortex of anesthetized rats (29). They are slower than those in vivo in primary motor and dorsal premotor cortices of monkeys (30) and in turtle visual cortex (31). (5) and theoretical studies (32), indicating that the resting state of the mammalian brain on this scale consists of multiple anticorrelated functional clusters.…”
Section: Results Of Simulationssupporting
confidence: 62%
“…These measures are similar to propagating neocortical waves observed in vitro (28) and in vivo in visual cortex of anesthetized rats (29). They are slower than those in vivo in primary motor and dorsal premotor cortices of monkeys (30) and in turtle visual cortex (31). (5) and theoretical studies (32), indicating that the resting state of the mammalian brain on this scale consists of multiple anticorrelated functional clusters.…”
Section: Results Of Simulationssupporting
confidence: 62%
“…Numerous studies in nonhuman primates have demonstrated significant task-related effects in the low beta band (4,5,(27)(28)(29), but except for the elegant studies of Tan and colleagues (30,31), oscillation during the postmovement period has not been analyzed in detail. Brief episodes of heightened spike activity at task end have been documented in both nonhuman primates and rodents (16)(17)(18)(19)(20)32).…”
Section: Discussionmentioning
confidence: 99%
“…basal ganglia | local field potentials | beta band | sequential movement | synchronization O scillations of brain activity in the beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) have been implicated in sensorimotor control and integration (1)(2)(3)(4)(5) and are pathologically synchronized and exaggerated in Parkinson's disease (6)(7)(8)(9)(10)(11). Although reports have published examples of very brief (<150 ms) bursts of beta-band oscillation (12)(13)(14)(15), the analysis of beta-band activity has focused primarily on data averaged over trials, which show variations in average beta-band power occurring on a time scale of seconds.…”
mentioning
confidence: 99%
“…However, much of the information about traveling waves is based on studies in anesthetized animals (53)(54)(55). Although recent developments in multielectrode array recording technology have enabled the detection of (γ) fast oscillatory waves in anesthetized preparations (56), it is only recently that traveling β-waves have been reported in the awake state (57,58). In a recent study, it was shown that the anisotropy of the cortical wiring may influence the spatiotemporal spike patterning (at least in the motor cortex) and that FS cells were found to fire more reliably in phase with the β-oscillation (59).…”
Section: Discussionmentioning
confidence: 99%